Estudo da viabilidade de migração da tecnologia satelital para tecnologia web, no âmbito da Escola Superior da Magistratura Tocantinense, para transmissão dos cursos realizados na modalidade a distância - Leite, Lily Sany Silva (Universidade Federal do Tocantins, 2021)
The present work presents a study of the feasibility of migration from satellite technology to web technology, within the scope of the Superior School of Magistracy Tocantinense (ESMAT), for transmission of courses taken in the distance learning modality. The study starts with the development of a bibliographic and documentary research on the theme, where it is presented: a brief history about Esmat; the use of distance education in the Brazilian Judiciary; a comparative study between satellite and web transmission technology. Next, Esmat's Distance Learning Technological Network is presented, showing the entire technological structure and procedures already used by the School for satellite and web transmission, as well as the teaching activities carried out in the distance mode. As for the methodological procedures, this research approached a qualitative contextualization, since it is based on deepening and explaining the procedures that culminated in the proposal of the theme; an applied research, since it can generate information and new knowledge regarding the use of technology for the transmission of courses in distance education; exploratory, in order to explain the feasibility of technology migration, through a bibliographic and documentary research; and classified as a case study, considering that this research focuses on the technology used within the scope of Esmat for transmission of distance education courses, with the documentary nature, because in order to understand the universe of the object of the research, it is necessary to analyze the institutional documents, such as reports, newsletters, projects, institutional videos and legal documents. This research has as its central axis Esmat, organ of the Court of Justice of the State of Tocantins, assuming the importance of this School in the Tocantinense Judiciary, whose mission is “To train and improve magistrates and civil servants in search of good practices and excellence in performance jurisdictional”; The workforce is distributed in 42 counties in the state of Tocantins and is made up of 2.704 servants, 115 judges and 11 judges. With this, we seek to present a study of the feasibility of migration of the technology used by Esmat for transmission of distance education courses, focusing on the migration from satellite transmission to transmission via web.